EXPRESSION OF GH GENE POLYMORPHISMS AND THEIR ASSOCIATION WITH GROWTH TRAITS OF LOCAL, EXOTIC BREED AND THEIR RECIPROCAL CROSSBRED CHICKENS USING MOLECULAR MARKERS - Ahmed, Lajan; Abdullah, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimedto characterize by using two genetic groups of chickens, which were Kurdish indigenous chickens (KK) and commercial Super Harco chickens which bred particularly for dualpurpose (SS),Four combinations were produced by diallel crossing between the two genotypes which are (KK, KS, SK, and SS).. The single nucleotide polymorphisms (SNPs) in the GH genes were identified between genotypes. Additionally, assessment oftheir belong to genotypes relationships with growth efficiency (body weight (BW) at hatching and 3,6,9, 12 weeks of age was carried on. The four genotypes were detected by using polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP) techniques by specific primers and restrictase for GH gene.Our data showed that the AA genotype had more values in KK and SK chickens while AB genotype were more in values in KS. The genotype BB was only more in SS (0.56) birds and no values in KK (0.04), KS (0.25) and SK (0.09) birds. The analysis of chi-square test indicated that SK, SS, males and femaleswhich arein (HWE) Hardy-Weinberg equilibrium (p